2022
DOI: 10.1155/2022/3570399
|View full text |Cite
|
Sign up to set email alerts
|

Posterior Capsule Opacification after Cataract Surgery via Implantation with Hydrophobic Acrylic Lens Compared with Silicone Intraocular Lens: A Systematic Review and Meta-Analysis

Abstract: Hydrophobic acrylic intraocular lens (IOL) is the most popular material in cataract surgery. Posterior capsule opacification (PCO) is a long-term complication of cataract surgery. It can impair vision and adversely affect the prognosis of IOL delamination. The objective of this study was to perform a systematic review and meta-analysis to provide an updated evaluation of long-term complications and visual function after implantation with hydrophobic acrylic and silicone intraocular lenses. PubMed, Embase, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 51 publications
0
11
0
Order By: Relevance
“…In this study, PCO diagnosis was established after a median of 12 months, ranging from 8.2 months to 26.3 months after cataract extraction. Ayuningtyas et al [8] found that the duration of the PCO diagnosis was established since surgery with a median of 21 months with a range from one month to 34 months, while Kwon et al [17] found the duration of the PCO diagnosis was established in 16 months after surgery with a range of 6 to 18 months. It can be concluded that the results obtained in this study were following previous research.…”
Section: Resultsmentioning
confidence: 99%
“…In this study, PCO diagnosis was established after a median of 12 months, ranging from 8.2 months to 26.3 months after cataract extraction. Ayuningtyas et al [8] found that the duration of the PCO diagnosis was established since surgery with a median of 21 months with a range from one month to 34 months, while Kwon et al [17] found the duration of the PCO diagnosis was established in 16 months after surgery with a range of 6 to 18 months. It can be concluded that the results obtained in this study were following previous research.…”
Section: Resultsmentioning
confidence: 99%
“…A meta-analysis study provided an assessment of 17 updated clinical studies of long-term complications and visual function after implantation of hydrophobic acrylic and silicone intraocular lenses from January 2000 to March 2021. The results of the analysis revealed a greater PCO value (Group 3: standardized mean difference: -0.59; CI: -0.90 to -0.28) and Nd: YAG capsulotomy rate (Group 3: hazard ratio (RR), 0.60; 95% CI, 0.40-0.89) for hydrophobic acrylic IOLs than silicone IOLs during long-term follow-up (≥6 years) [18].…”
Section: Major Clinical Findingsmentioning
confidence: 94%
“…Posterior capsular opacification (PCO) is a common long-term complication that develops after cataract surgery and causes findings such as decreased visual acuity, photophobia, and glare [1][2][3]. The incidence of PCO after cataract surgery has been reported to vary between 2.5% and 50% [4].…”
Section: Introductionmentioning
confidence: 99%
“…PCO occurrence may depend on patient-related factors, the surgical technique applied, or the characteristics of the intraocular lens (IOL) implanted [2][3][4][5]. Not only the material of IOL, but also its edge profile and localization, are important in the formation of PCO [4,5].…”
Section: Introductionmentioning
confidence: 99%